Physical growth and nutritional status of Tsimane's Amerindian children of lowland Bolivia - Foster, Z.; Byron, Elizabeth; Reyes-Garcia, Victoria; Huanca, Thomas; Vadez, Vincent; Apaza, Lilian; Perez Eddy; Tanner, S.; Gutierrez, Y.; Sandstrom, B.; Yakhedts, A.; Osborn, C.; et al. (Wiley, 2005)
This study examines patterns of growth and nutritional status of indigenous Tsimane' children under 9 years of age (n = 199 boys and 210 girls), based on a cross‐sectional sample from 58 villages from the Beni Deparment of lowland Bolivia. Compared with US children, Tsimane' children are quite short, with linear growth tracking at or below the US 5th centile in both sexes. The prevalence of low height‐for‐age (“stunting;” HA Z‐scores ≤−2) is 52% in boys and 43% in girls. In contrast, weight‐for‐height in Tsimane' children approximates the US median, with the prevalence of low weight‐for‐height (“wasting”; WH Z‐scores ≤−2) being only 4% and 6% in boys and girls, respectively. Tsimane' boys and girls are leaner than their US peers, but their levels of body fatness are not so low as to indicate severe energy stress. Arm muscularity of Tsimane' children is similar to that of their US age peers, and this suggests that they are not experiencing acute protein malnutrition. Variation in measures of nutritional status of Tsimane' children is modestly correlated with village‐level differences. Degree of isolation, as measured by distance to urban centers or to primary forest, was not a strong predictor of children's anthropometric status. Rather, in both boys and girls, nutritional status was most strongly associated with number of teachers in the village, a measure of access to education. Comparative analyses indicate that high levels of statural growth stunting are common among indigenous populations throughout lowland South America. This problem appears to be largely attributable to poor dietary quality (diets low in key micronutrients) and high disease loads. Further research is needed to identify the specific causes and potential interventions for the high rates of childhood growth stunting in this region. Am J Phys Anthropol 126:343–351, 2005. © 2004 Wiley‐Liss, Inc.